AI-Driven Traffic Accidents: A Comparative Legal Study - Muhammad Arifin; Mursyid Mursyid (Contemporary Issues on Indonesian Social Justice and Legal Reform, 2025)
This research explores the evolving legal landscape surrounding criminal liability in traffic accidents involving AI-driven vehicles. The study aims to analyze the conceptual and practical challenges posed by assigning criminal responsibility in such cases, particularly focusing on the comparison of legal frameworks at the international level. The research methodology employed is a normative legal study, utilizing a comparative approach to analyze existing laws and regulations related to AI-driven vehicles in the United States, the European Union, and Japan. The study examines the theoretical foundations of criminal liability, including mens rea and actus reus, in the context of AI technology. The findings of this research highlight the need for innovative legal adaptations to address the unique challenges posed by AI-driven vehicles. Concepts such as vicarious liability and ethical decision-making algorithms emerge as potential solutions to ensure accountability and safety in autonomous transportation. The study also underscores the importance of international cooperation in harmonizing legal standards to facilitate the global deployment of AI-driven vehicles.